Stability of Staphylococcus aureus Phage ISP after Freeze-Drying (Lyophilization) - Merabishvili, Maia; Vervaet, Chris; Pirnay, Jean-Paul; De Vos, Daniel; Verbeken, Gilbert; Mast, Jan; Chanishvili, Nino; Vaneechoutte, Mario (PLOS ONE, 2013)
Staphylococcus aureus phage ISP was lyophilized, using an Amsco-Finn Aqua GT4 freeze dryer, in the presence of six different stabilizers at different concentrations. Stability of the lyophilized phage at 4°C was monitored up to 37 months and compared to stability in Luria Bertani broth and physiological saline at 4°C. Sucrose and trehalose were shown to be the best stabilizing additives, causing a decrease of only 1 log immediately after the lyophilization procedure and showing high stability during a 27 month storage period.